2017
DOI: 10.1016/j.jmb.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Induces MiR-7 Processing through Remodeling of Pri-MiR-7/Protein Complex

Abstract: MicroRNAs (miRs) play a vital role in governing cell function, with their levels tightly controlled at transcriptional and post-transcriptional levels. Different sets of RNA-binding proteins interact with primary miRs (pri-miRs) and precursor-miR transcripts (pre-miRs), controlling their biogenesis post-transcriptionally. The Hu antigen R (HuR)-mediated binding of Musashi homolog2 (MSI2) to the conserved terminal loop of pri-miR-7 regulates the levels of brain-enriched miR-7 formation in a tissue-specific mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…4F). Although it is still in the early stages for our understanding of the regulatory mechanisms of individual miRNA expression, it was shown that miR-7 was increased by estrogen (Masuda et al 2012), oleic acid (Kumar et al 2017), and curcumin (Feng et al 2017) in some cancer cells, while miR-141/ 200 expression was induced by oxidative stress such as hydrogen peroxide (Magenta et al 2011;Mateescu et al 2011). It is obvious that the regulation of IRP-IRE interactions by cellular iron status governs the stability of TfR1 mRNA; however, it is conceivable that expression changes in these miRNAs in response to environmental cues and in different tissues ultimately determine the stability of TfR1 mRNA and cellular iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…4F). Although it is still in the early stages for our understanding of the regulatory mechanisms of individual miRNA expression, it was shown that miR-7 was increased by estrogen (Masuda et al 2012), oleic acid (Kumar et al 2017), and curcumin (Feng et al 2017) in some cancer cells, while miR-141/ 200 expression was induced by oxidative stress such as hydrogen peroxide (Magenta et al 2011;Mateescu et al 2011). It is obvious that the regulation of IRP-IRE interactions by cellular iron status governs the stability of TfR1 mRNA; however, it is conceivable that expression changes in these miRNAs in response to environmental cues and in different tissues ultimately determine the stability of TfR1 mRNA and cellular iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid (a natural monounsaturated fatty acid produced by plants and animal cells) inhibits the RNA-binding activity of Musashi RNA-binding protein 2 (MSI2), a negative regulator of pri-mir-7 processing, by binding to its N-terminal RRM (Choudhury et al 2013;Clingman et al 2014). Thus, the action of oleic acid could be used to disrupt the formation of a negative regulatory complex and lead to stimulation of miR-7 biogenesis (Kumar et al 2017). Such strategies could reduce the levels of miR-7 target genes such as the EGFR oncogene, to potentially alleviate its deleterious effects in high-grade glioblastomas, where miR-7 is post-transcriptionally down-regulated (Kefas et al 2008).…”
Section: Synthetic and Natural Inhibitors Of Mirna Biogenesismentioning
confidence: 99%
“…Different aspects have to be considered when explaining this discrepancy between in vivo and in vitro results especially for miR‐7. On the one hand, other factors regulating the miR‐7 expression have been described, for instance INF‐γ or oleic acid . The in vitro experiments were performed in the absence of fetal calf serum (FCS) which is different from the situation in vivo , were many cytokines or growth factors are present.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, other factors regulating the miR-7 expression have been described, for instance INF-γ or oleic acid. 48,49 The in vitro experiments were performed in the absence of fetal calf serum (FCS) which is different from the situation in vivo, were many cytokines or growth factors are present. Since it is known that cytokines affect the expression of miRNAs, it was tried to minimize the impact of these factors on the results of the in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%